An attempt to replace orthodox sacraments with new Soviet rituals in the 1960–80s: a case study of Perm region - Andrey Sapsay (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article deals with introducing new civil ritualism by the Soviet authorities. The new Soviet holidays and rituals were to become an alternative to the Orthodox sacraments and a form of struggle against religion. The author analyzes quantitative indicators of both non-religious rituals (ceremonial registration of marriage and birth, civil memorial service) and Orthodox sacraments (baptism, wedding, funeral rite) performed by the population of the Perm region in the 1960s - early 1980s. It has been established that as a result of the adopted laws, the involvement of administrative resources, public figures and widespread atheistic propaganda, they gradually managed to introduce new non-religious rituals in the Perm region in the period from 1964 to 1983. Within the framework of the study, various forms and methods used to introduce civil rituals and to reduce the Orthodox sacraments are for the first time investigated on the basis of archival sources and literature. They are sociological research, educational work in schools, the persecution of the clergy and believers, etc. It is noted that local authorities themselves, trying to comply with the requirements of the legislation on cults, admitted the facts of its gross violation. Nevertheless, the main goal of the anti-church policy - the replacement of the Orthodox sacraments and rites with the new Soviet rituals - was not fulfilled; the number of Orthodox sacraments and rites practically did not decrease. Moreover, in the late 1970s, some weakening of control over the activities of church organizations and increase in the number of religious rituals was observed everywhere. It was facilitated by a more liberal attitude of the local authorities towards the Russian Orthodox Church, strengthening of educational activities of the clergy, and the population's commitment to Orthodox traditions. The statistical data presented in the work allow the author to conclude that the introduction of new civil rituals could not oust the sacraments and rites performed in the church from the life of the Orthodox population.